Different proteomic strategies to identify genuine Small Ubiquitin-like MOdifier targets and their modification sites in Trypanosoma brucei procyclic forms - Iribarren, Paula Ana (2015)
SUMOylation is an important post-translational modification conserved in eukaryotic organisms. In Trypanosoma brucei, SUMO (Small Ubiquitin-like MOdifier) is essential in procyclic and bloodstream forms. Furthermore, SUMO has been linked to the antigenic variation process, as a highly SUMOylated focus was recently identified within chromatin-associated proteins of the active variant surface glycoprotein expression site. We aimed to establish a reliable strategy to identify SUMO conjugates in T.brucei. We expressed various tagged variants of SUMO from the endogenous locus. His-HA-TbSUMO was useful to validate the tag functionality but SUMO conjugates were not enriched enough over contaminants after affinity purification. A Lys-deficient SUMO version, created to reduce contaminants by Lys-C digestion, was able to overcome this issue but did not allow mapping many SUMOylation sites. This cell line was in turn useful to demonstrate that polySUMO chains are not essential for parasite viability. Finally, a His-HA-TbSUMOT106K version allowed the purification of SUMO conjugates and, after digestion with Lys-C, the enrichment for diGly-Lys peptides using specific antibodies. This site-specific proteomic strategy led us to identify 45 SUMOylated proteins and 53 acceptor sites unambiguously. SUMOylated proteins belong mainly to nuclear processes, such as DNA replication and repair, transcription, rRNA biogenesis and chromatin remodelling, among others.